Abstract: Actinomycete strains isolation and selection from Algerian saline soils as environmentfriendly tool for Solanum lycopersicum fertilization. Issue (2020)Special Issues (2020) - Djebaili, Rihab; Pellegrini, M.; Smati, M.; Bernardi, M.; Gallo, M. Del; Kitouni, M.
No abstract available